End of life care for long-term neurological conditions: A meta-ethnographic review of the experiences of informal carers. (February 2021) - Toze, Michael; Ray, Mo; George, Thomas; Sisson, Kelly; Nelson, David
Background: Family and friends are key providers of care for people living with a long-term neurological condition. Neurological conditions are a significant global contributor to disability and premature death. However, previous research suggests carers often struggle to access appropriate support at end of life. Aims: This review sought to synthesise qualitative studies discussing end-of-life and palliative issues for informal carers supporting people living with neurological conditions. Design: This was a meta-ethnographic synthesis of 38 qualitative studies discussing end-of-life and palliative issues for informal carers supporting people living with long-term neurological conditions. Data Sources: Qualitative articles published after January 2010 in English, addressing carers of people with long-term neurological conditions with regard to palliative care, end of life and/or bereavement. Papers were excluded if it was not possible to separately assess the views of carers. Quality appraisal was not undertaken, but consideration was given to research context. Results: Across the papers, five key themes were identified: the future (un)certainties in the progression of life-limiting neurological conditions; an information paradox of not receiving the right information at the right time; access to support; carers' roles in decision making around end of life; and maintaining continuity while facing change and disruption in day-to-day living. Conclusions: Given the broad agreement on the challenges faced by carers of people living with long-term neurological conditions, future research should consider opportunities to improve information and support for this group, and the development and evaluation of practical models of service delivery.